A New Boost DC-DC Converter Based on a Coupled Inductor and Voltage Multiplier Cells - Mahmoodreza Eskandarpour Azizkandi; Farzad Sedaghati; Hossein Shayeghi (International Journal of Industrial Electronics, Control and Optimization, 2019)
A new non-isolated, coupled-inductor, single-switch boost DC-DC converter for photovoltaic (PV) power application is introduced in this paper. A coupled inductor and voltage multiplier cells is used in the presented converter to obtain a high voltage conversion ratio. Also, a passive clamp circuit is applied in the converter structure to reduce voltage stress of the power switch. This leads to using a power switch with lower on-state resistance in the converter which decreases the conduction loss. In addition, zero current switching (ZCS) condition for the power switch is achieved due to the use of the clamp circuit. Several advantages such as low operating duty cycle, high voltage conversion ratio, reduced voltage stress of semiconductors, low turn ratio for the coupled inductor, leakage inductance reverse recovery and high efficiency operation make the presented converter suitable for renewable energy applications. The steady state operation of the suggested structure in continuous conduction mode (CCM) and discontinuous conduction mode (DCM) is expressed and analyzed. Then, the presented topology is compared with several similar high gain topologies to prove its advantages. Finally, experimental measurement results of a laboratory prototype of the proposed DC-DC converter with about 213W output power and 435V output voltage at 50 kHz switching frequency are presented to corroborate its feasibility and performance.